GROWTH PERFORMANCE OF LAYING HENS FED DIETS CONTAINING DIFFERENT LEVELS OF PALM KERNEL MEAL AND COPRA MEAL - Gunawan, Aynan Hismafanti; Sundu, Burhanudin; Hatta, Ummiani; Sugiarto, Sugiarto; Marfuah, N. Marfuah (Fakultas Peternakan, Universitas Padjadjaran, 2025)
AbstractFeed plays an important role in livestock metabolism, especially to support growth, maintain body condition, and production. Therefore, efforts are needed to find high-quality feed ingredients that are easy to obtain, sustainably available, do not compete with human needs, are non-toxic, and economical. One alternative feed ingredient that can be optimized to reduce feed costs is industrial waste, such as coconut meal and palm kernel meal. This research was conducted at the Laboratory of the Faculty of Animal Husbandry and Fisheries, Tadulako University, Palu, for five weeks, namely from March 19, 2022 to May 20, 2022. A total of 80 laying hens aged 64 weeks were used in this study, with five treatments and four replications. This study used a completely randomized design (CRD) with further analysis using the Honestly Significant Difference Test (HSD). The variables observed included feed consumption (g), egg production (g), feed conversion, energi intake (kcal), and protein intake (g). The results showed that the treatment had a very significant effect on feed consumption (P<0.01), and had a significant effect on egg production, feed conversion, energy intake, and protein intake (P<0.05). From the results of the study it can be concluded that the addition of 5% palm kernel meal and 5% coconut meal is the most recommended combination as an alternative feed ingredient in laying hen rations.Keywords: Copra meal, laying hens, palm kernel meal